The Usage of Information and Communication Technology in Nigeria Primary Schools:Problems and Prospects - Abass, Bada Tayo; Ayo, Ojediran (Richtmann Publishing, 2012)
The paper investigated the usage of Information and Communication Technology (ICT) in Osun State PrimarySchools. Questionnaires were administered to 100 primary school teachers. The questionnaires were designed to find out theroles of ICT in teaching and learning and problems associated with its usage in the primary schools.Results showed that majorityof the primary school teachers in Osun State lack the basic skills required for the usage of computer. In addition, the teacherssupport the implementation of ICT in the primary schools. The results also revealed that the ICT is facing with problems in OsunState Primary Schools.